Perspectives of the cooperation between Vietnam and the Eurasian Economic Union (EAEU) - Novikova E.S.; Nguyen Phu Huu (Vostočnaâ Aziâ: fakty i analitika, 2024)
This paper's purpose is to examine the cooperation between the Eurasian Economic Union (EAEU) and Vietnam, with a focus on its significance for the EAEU in ASEAN. The present state of affairs is considered from the perspective of Vietnam's ties with the EAEU, which includes Russia, Belarus, Kazakhstan, Kyrgyzstan, and Armenia. The study is based on the dynamics of Vietnam's trade turnover with each of these countries, including import and export of goods, the structure of their categories, investment volume, and the number of investment projects in each country. The analysis of the Free Trade Agreement (FTA) between Vietnam and the EAEU is another focus of the article, as well as identifying the FTA's function and its possible prospects. An independent attempt is made to define Vietnam's primary benefits and obstacles when compared with other ASEAN members. The paper’s findings can be applied to enhance bilateral relations between Vietnam and EAEU countries.